AVALIAÇÃO CARDIOVASCULAR DE CÃES NATURALMENTE INFECTADOS POR Ehrlichia canis - Rejane Diniz dos santos (2022)
Canine monocytic ehrlichiosis, caused by the bacterium E. canis, can cause severe anemia in dogs and directly affect the cardiovascular system. Depending on the severity and clinical phase of the disease, cardiac lesions such as myocarditis and arrhythmias may be observed. The electrocardiogram allows the diagnosis of heart rhythm disorders and echocardiogram assists in the detection of heart diseases and in the evaluation of ventricular systolic and diastolic functions. In addition to these, troponin I is used as a marker of cardiac injury, as it is released into the bloodstream when myocardial injury occurs, remaining circulating for as long as the lesion persists. Thus, the present study aimed to evaluate possible cardiovascular lesions in dogs naturally infected with E canis in the subclinical phase. The present study evaluated 35 dogs, 25 of which were positive for canine ehrlichiosis on PCR, of which 16 were females and 9 males. All patients underwent the same tests and divided in two groups, (CG) control group and (GD), sick group. Animals with comorbidities and structural heart diseases were excluded from the study. The tests and parameters evaluated were: blood count, platelet and red blood cell count, globular volume, echocardiogram with the variables of systolic function E%, FS%, MAPSE, TAPSE and diastolic function TDI E ́/A ́L, electrocardiogram for heart rhythm analysis and the troponin I biomarker. From the results it was possible to evaluate the possible alterations that E. canis cause in the cardiovascular system. Parameters such as systolic or diastolic rhythm and function evaluated did not present alterations in animals of the GD group when compared to the CG. However, when we evaluated the cTnI in this study, animals of the GD presented biomarker values 12.6 times higher (95%CI=2.09-76.7) when compared with healthy not infected animals from CG. Keywords: canines, canine monocytic ehrlichiosis, heart rate, myocardium, biomarker